Het archeologisch onderzoek op de Hopmarkt te Aalst (Oost-Vlaanderen) - De Maeyer, Wouter; Van Cauwenbergh, Stijn; Klinkenborg, Sigrid; Taelman, Evelien; Cherretté, Bart (Archaeologia mediaevalis, 2012)
Karmelietenklooster Aalst